The eINTACT system dissects bacterial exploitation of plant osmosignalling to enhance virulence - You, Yuan (2022)
Bacteria inject effector proteins into host cells to manipulate cellular processes that promote disease. Since bacteria deliver minuscule amounts of effectors only into targeted host cells, it is technically challenging to capture effector-dependent cellular changes from bulk-infected host tissues. Here, we report a new technique called effector-inducible isolation of nuclei tagged in specific cell types (eINTACT), which facilitates affinity-based purification of nuclei from Arabidopsis plant cells that have received Xanthomonas bacterial effectors. Analysis of purified nuclei reveals that the Xanthomonas effector XopD manipulates the expression of Arabidopsis abscisic acid signalling-related genes and activates OSCA1.1, a gene encoding a calcium-permeable channel required for stomatal closure in response to osmotic stress. The loss of OSCA1.1 causes leaf wilting and reduced bacterial growth in infected leaves, suggesting that OSCA1.1 promotes host susceptibility. eINTACT allows us to uncover that XopD exploits host OSCA1.1/abscisic acid osmosignalling-mediated stomatal closure to create a humid habitat that favours bacterial growth and opens up a new avenue for accurately elucidating functions of effectors from numerous gram-negative plant bacteria in native infection contexts.